De-escalation of surgical and radiation treatment in elderly luminal breast cancer patients, single institution report and review of the evidence - Yasmin Korzets; Marian Khatib; Hadar Goldvaser; Yehiel Hibshoosh; Alla Nikolaevski-Berlin; Ido Wolf; Viacheslav Soyfer (World Journal of Surgical Oncology)
Abstract Background De-intensification of anti-cancer therapy without significantly affecting outcomes is an important goal. Omission of axillary surgery or breast radiation is considered a reasonable option in elderly patients with early-stage breast cancer and good prognostic factors. Data on avoidance of both axillary surgery and radiation therapy (RT) is scarce and inconclusive. Methods A retrospective cohort study comprising all women aged 70 years and older diagnosed with early, hormone receptor (HR) positive, HER2-negative breast cancer treated with breast-conserving surgery (BCS) without sentinel lymph node biopsy (SLNB) and RT in a large tertiary center (between 2016 and 2021). Data on patient and tumor characteristics as well as outcomes including local recurrence, loco-regional recurrence, distant metastases, and death were extracted. Disease free survival (DFS) was assessed by Kaplan-Meier analysis. The Cox proportional hazard regression model was performed to identify factors (demographic and clinical characteristics of the patients) that predict the disease recurrence or death. Results A total of 100 women were included, median age of patients was 81. All patients had clinically node-negative disease with a median tumor size was 13 mm. Five (5%) women had lymphovascular invasion. At a median follow-up of 3.9 years, there were 7 (7%) recurrences, 4 local, 2 local-regional, and one distant. The median DFS for the entire group was 42 months (11–128). Eight patients (8%) died, 5 of them for reasons unrelated to breast cancer (3 of unknown reason). Tumor size larger than 13 mm was associated with significantly worse DFS (HR = 4.02, 95% CI 1.08–14.99, p = 0.04). Conclusion Omission of both SLNB and adjuvant RT is feasible in elderly, early breast cancer patients with small luminal tumors.